Missing interstellar sulfur in inventories of polysulfanes and molecular octasulfur crowns - Ashanie Herath; Mason McAnally; Andrew M. Turner; Jia Wang; Joshua H. Marks; Ryan C. Fortenberry; Jorge C. Garcia-Alvarez; Samer Gozem; Ralf I. Kaiser (Nature Communications)
Abstract The disparity between predicted sulfur abundances and identified reservoirs of sulfur in cold molecular clouds, also known as the sulfur depletion problem, has remained an ongoing debate over decades. Here, we show in laboratory simulation experiments that hydrogen sulfide (H2S) can be converted on ice-coated interstellar grains in cold molecular clouds through galactic cosmic rays processing at 5 K to sulfanes (H2Sn; n = 2–11) and octasulfur (S8). This locks the processed hydrogen sulfide as high-molecular weight sulfur-containing molecules thus providing a plausible rationale for the fate of the missing interstellar sulfur. These sulfuretted molecules may undergo fractionated sublimation once the molecular cloud transforms into star forming regions. The isomeric identification of octasulfur rings (S8) coincides with the recent identification of elementary sulfur in the carbonaceous asteroid (162173) Ryugu, thus providing compelling evidence on the link between sulfur in cold molecular clouds and in our Solar System with, e.g., the Taurus Molecular Cloud (TMC) potentially accumulating an equivalent of 350 Earth masses of octasulfur.